1900 Ohio Gen. and Local Acts 730, Act to provide a license on trades, business and professions carried on and for the use of streets . . . §§ 24-25 (vol. 94) - (:unkn) unknown (My University, 1900)
All keepers or owners of gun powder magazines shall pay a license fee of one hundred dollars ($100) per annum, and shall notify the chief of the fire department, in writing, of the place where the same is kept or stored; but no license shall be issued under this section without the consent of the mayor. § 25. All keepers of shooting galleries shall pay a license fee of fifty dollars ($50) per annum, or for a less period of one year at a rate of ten dollars ($10) per month, no license to be issued for a less period than one month.
Keywords: TAX - PROPERTY OR SALES